Safety and efficacy of intra-arterial fibrinolytics as adjunct to mechanical thrombectomy: a systematic review and meta-analysis of observational data. (29th January 2021) - Kaesmacher, Johannes; Meinel, Thomas Raphael; Kurmann, Christoph; Zaidat, Osama O; Castonguay, Alicia C; Zaidi, Syed F; Mueller-Kronast, Nils; Kappelhof, Manon; Dippel, Diederik W J; Soudant, Marc; Bracard, Serge; Hill, Michael D; et al.
Abstract : Background: Achieving the best possible reperfusion is a key determinant of clinical outcome after mechanical thrombectomy (MT). However, data on the safety and efficacy of intra-arterial (IA) fibrinolytics as an adjunct to MT with the intention to improve reperfusion are sparse. Methods: We performed a PROSPERO-registered (CRD42020149124) systematic review and meta-analysis accessing MEDLINE, PubMed, and Embase from January 1, 2000 to January 1, 2020. A random-effect estimate (Mantel-Haenszel) was computed and summary OR with 95% CI were used as a measure of added IA fibrinolytics versus control on the risk of symptomatic intracranial hemorrhage (sICH) and secondary endpoints (modified Rankin Scale ≤2, mortality at 90 days). Results: The search identified six observational cohort studies and three observational datasets of MT randomized-controlled trial data reporting on IA fibrinolytics with MT as compared with MT alone, including 2797 patients (405 with additional IA fibrinolytics (100 urokinase (uPA), 305 tissue plasminogen activator (tPA)) and 2392 patients without IA fibrinolytics). Of 405 MT patients treated with additional IA fibrinolytics, 209 (51.6%) received prior intravenous tPA. We did not observe an increased risk of sICH after administration of IA fibrinolytics as adjunct to MT (OR 1.06, 95% CI 0.64 to 1.76), nor excess mortality (0.81, 95% CI 0.60 to 1.08). Although the mode of reporting was heterogeneous, some studies observed improved reperfusion after IA fibrinolytics. Conclusion: The quality of evidence regarding peri-interventional administration of IA fibrinolytics in MT is low and limited to observational data. In highly selected patients, no increase in sICH was observed, but there is large uncertainty.